Aspectos sintático, semântico e pragmático do ICMS-Importação: análise das alterações promovidas pela EC 33/2001 - Brofman, Paula Eschholz Ribeiro (2014)
Constitutional Amendment No. 33, dated December 12, 2001 changed the wording of art. 155, § 2, section IX, paragraph a, of the Brazilian Federal Constitution of 1988. Unsurprisingly the commitment of the states and the Federal District for all tax and any entry of goods and commodities in the country. They lacked, however, a constitutional approval for this. It was then that the Constitutional Amendment 33 modified the constitutional archetype of ICMS in order to make it focus on any entry of goods or merchandise in the country. These changes resulted in heated debates on the doctrine of the Tax Law, which saw the creation of a new tax, in the guise of ICMS, enter the legal world through an Amendment to the Constitution. Is that musty derived constituent power is not fully free to modify the constitution to their own pleasure, there are parameters set by the original power that must be respected, otherwise it would incur unconstitutional. Thus, this paper intends to perform a syntactic, semantic and pragmatic analysis of the exaction in order to demonstrate the main changes brought about by Constitutional Amendment No. 33, 2001, marginalized original guidelines and the consequent alterations to the unconstitutionality of the import-ICMS